Direct Costs of Occupational Asthma in Quebec between 1988 and 2002 - Jean-Luc Malo; Jocelyne L’Archevêque; Heberto Ghezzo (Canadian Respiratory Journal)
BACKGROUND: Forty to 70 cases of occupational asthma due to sensitization to an agent present in the workplace are accepted each year by the Commission de la santé et de la sécurité du travail, the Quebec medicolegal agency.